Asymmetric Dopamine Transporter Loss Affects Cognitive and Motor Progression in Parkinson's Disease. Issue 10 (14th June 2021) - Fiorenzato, Eleonora; Antonini, Angelo; Bisiacchi, Patrizia; Weis, Luca; Biundo, Roberta
ABSTRACT: Background: Asymmetric hemispheric loss of dopaminergic neurons is one of the characteristic features of Parkinson's disease (PD). However, it is still debated if right or left asymmetry differently affects cognitive and motor progression. Objectives: The objective of this study was to investigate, for the first time, the relevance of dopamine transporter (DAT) asymmetry on cognitive and motor manifestations at onset and at 4‐year progression in drug‐naïve PD. Methods: From the Parkinson's Progression Markers Initiative multicenter cohort, we identified 249 right‐handed patients with PD with baseline asymmetry greater than 20% in putamen DAT binding at single‐photon emission computed tomography. A predominant putamen asymmetry was found on the left in 143 patients (PD‐left), and on the right side in 106 patients (PD‐right); we compared them with 196 healthy controls. Patients were followed longitudinally (2‐year and 4‐year visits), examining their clinical, cognitive, and imaging data. Results: At baseline, the PD‐left group showed worse performance on the Symbol Digit Modality Test, an attention and processing‐speed test, and lower cerebrospinal fluid β‐amyloid levels than the PD‐right group. These differences were maintained at follow‐up, declining over time in both groups. By contrast, the PD‐right group showed greater motor impairment at baseline, which increased over 4 years. Striatal DAT binding decreased over time in both groups, but the PD‐right group showed a steeper decline, particularly during the first 2‐year follow‐up. Putaminal asymmetry assessed at baseline was maintained over time. Conclusions: These findings suggest that hemispheric asymmetric dopaminergic denervation influences PD cognitive and motor performance as well as progression. Predominant right hemisphere nigrostriatal dopaminergic loss is associated with greater motor severity, whereas more pronounced left hemisphere denervation affects cognitive manifestations at onset and their progression. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society